Acute otitis media guidelines in selected developed and developing countries: uniformity and diversity. Issue 5 (6th September 2016) - Ovnat Tamir, Sharon; Shemesh, Shay; Oron, Yahav; Marom, Tal
Abstract : Background: Acute otitis media (AOM) is a common childhood disease, with an enormous economic and healthcare-related burden. Guidelines and consensus papers for AOM diagnosis and management were published in many countries. Our objective was to study the differences and similarities between these protocols in developing and developed countries. Methods: The keywords: 'acute otitis media' AND 'children' AND ['treatment' or 'management'] AND ['guideline' or 'consensus'] were used in various electronic databases between 1 January 1989 through 31 December 2015. Overall, 99 sources from 62 countries were retrieved: 53 from 22 developed countries, and 46 from 40 developing countries. Representative guidelines from America (the USA, Argentina), Europe (Italy, Moldova), Africa (South Africa, Tanzania, Ethiopia), Asia (Japan, Afghanistan, Sri Lanka), and Oceania (South Australia, Fiji) were compared. Results: Paediatric societies publish guidelines in most developed countries; in developing countries, the Ministry of Health usually initiates guideline formulation. Most guidelines use the same diagnostic criteria and offer watchful waiting in mild–moderate scenarios. Amoxicillin is the suggested first-line antibiotic, whereas options for second-line and third-line therapies vary. Duration of therapy varies and is usually age dependent: 5–7 days for children <2 years and 10 days for children >2 years in developed countries, while duration and age groups vary greatly in developing countries. Reduction of AOM risk factors is encouraged in developed countries, but rarely in developing countries. Conclusions: Guidelines for AOM from developing and developed countries are similar in many aspects, with variation in specific recommendations, due to local epidemiology and healthcare accessibility. Formulation of regional guidelines may help reduce AOM burden.